Global Budget Payment - Bradley Chen MD, ScD; Victoria Y. Fan ScD (SAGE Publishing, 2016)
To control ever-increasing costs, global budget payment has gained attention but has unclear impacts on health care systems. We propose the CAP framework that helps navigate 3 domains of difficult design choices in global budget payment: Constraints in resources (capitation vs facility-based budgeting; hard vs soft budget constraints), Agent-principal in resource allocation (individual vs group providers in resource allocation; single vs multiple pipes), and Price adjustment. We illustrate the framework with empirical examples and draw implications for policy makers.